The impact of educational intervention on attitude towards organ donation among healthcare workers in five hospitals in Malaysia - Wan Muhd Shukeri, Wan Fadzlina; Mazlan, Mohd Zulfakar; Kamaruzaman, Lydia; Budiman, Maryam; Mohamad Yusof, Aliza; Ramly, Nur Fariza; Nanyan, Suhaila; Wan Ali, Wan Ahmad Syahril Rozli; Abd Halim, Nurul Huda; Mohd Sharif, Nur Hidayati; Abdul Hafidz, Muhammad Iqbal (Elsevier, 2022)
Introduction : The attitude of healthcare workers (HCW) are essential in influencing organ donation rates. Objective : The study aimed to assess the impact of educational intervention on attitudes towards organ donation among HCW. Methodology : A questionnaire-based interventional study was conducted among 458 HCW from five hospitals in Malaysia. A 26-item self-administered questionnaire was distributed online as a pre-intervention test. Afterwards, the respondents went through a website-based educative materials about organ donation and answered the same questionnaire again. Results : A total of 345 (75.3%) respondents completed the tests. Their attitude towards organ donation was positive pre-intervention. Following it, respondents expressed increase willingness to donate organs (P = 0.008) and their relatives’ organs (P <0.001); were more willing to adopt organ donation as part of the end-of-life care (P = 0.002) and were more comfortable to talk to relatives about organ donation (P = 0.001). There was increased willingness to admit patients to the Intensive Care unit for facilitating organ donation (P = 0.007); to employ the same resources to maintain a potential brain-dead donor (P <0.001); and to support organ donation if they or their relatives have end-stage organ failure (P = 0.008). However, there was increased negative attitude regarding association between organ donation with healthcare failure (P = 0.004), and with pain (P = 0.003). The positive attitude scores were higher following the intervention (P <0.001). Conclusion : An educational website-based intervention was able to improve HCW attitudes towards organ donation although some potential improvements are required.